Direct X-Ray Microtomography Observation Confirms the Induction of Embolism upon Xylem Cutting under Tension. Issue 1 (6th November 2014) - Torres-Ruiz, José M.; Jansen, Steven; Choat, Brendan; McElrone, Andrew J.; Cochard, Hervé; Brodribb, Timothy J.; Badel, Eric; Burlett, Regis; Bouche, Pauline S.; Brodersen, Craig R.; Li, Shan; Morris, Hugh; et al.
Abstract : Direct visualization shows enhanced embolism of xylem samples when they are collected under tension .